Computational challenges, tools, and resources for analyzing co‐ and post‐transcriptional events in high throughput. (16th December 2014) - Bahrami‐Samani, Emad; Vo, Dat T.; de Araujo, Patricia Rosa; Vogel, Christine; Smith, Andrew D.; Penalva, Luiz O. F.; Uren, Philip J.
<x xml:space="preserve">Abstract</x> Co‐ and post‐transcriptional regulation of gene expression is complex and multifaceted, spanning the complete RNA lifecycle from genesis to decay. High‐throughput profiling of the constituent events and processes is achieved through a range of technologies that continue to expand and evolve. Fully leveraging the resulting data is nontrivial, and requires the use of computational methods and tools carefully crafted for specific data sources and often intended to probe particular biological processes. Drawing upon databases of information pre‐compiled by other researchers can further elevate analyses. Within this review, we describe the major co‐ and post‐transcriptional events in the RNA lifecycle that are amenable to high‐throughput profiling. We place specific emphasis on the analysis of the resulting data, in particular the computational tools and resources available, as well as looking toward future challenges that remain to be addressed. WIREs RNA 2015, 6:291–310. doi: 10.1002/wrna.1274 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.